Final Demonstration of the Co-Identity of Lipiarmycin A3 and Tiacumicin B (Fidaxomicin) through Single Crystal X-ray Analysis - Stefano Serra; Luciana Malpezzi; Angelo Bedeschi; Claudio Fuganti; Piera Fonte (MDPI AG, 2017)
Lipiarmycin A3 and tiacumicin B possess the same chemical structure and have been considered identical till recently, when some authors have suggested the possibility of a minor difference between the chemical structures of the two antibiotics. In this work we performed a comparative X-ray analysis of lipiarmycin A3 and tiacumicin B. Although the commercial samples of the aforementioned compounds crystallize into two different crystal systems-evidently due to the different crystallization conditions-their chemical structures are identical. These results confirmed the previous assigned chemical structure of lipiarmycin A3 and its absolute configuration as well as its co-identity with the chemical structure of tiacumicin B, providing the definitive proof that these pharmaceutical compounds are identical in all respects.